HUBUNGAN LINGKUNGAN KERJA, DISIPLIN KERJA, DAN KINERJA KARYAWAN - Diah Indriani Suwondo; Eddy Madiono Sutanto (Management Study Program, Faculty of Business and Economics, Petra Christian University, 2015)
This study was aimed to know the influence of work environment and work dicipline to employee performance. This type of research was quantitiative research. This study used census method, which taken all the population to survey respondents. The number of employee were 40 people. The techniques of processing and analysis data used validity test, reliability test, classic assumption test, descriptive analysis, cross tabulation, linear regression analysis, and coefficient of determination analysis. The study stated that the influence of work environment and work discipline to employee performance of bank’s employees in Malang city had influence by individually and influence by simultaneously. A comfortable work environment and the high level of work discipline will to improve employee performance.